Use of telemedicine consultations in rheumatology during the COVID-19 pandemic - O. V. Teplyakova; A. A. Morozova (Современная ревматология)
Objective: to study the practice of organizing and conducting telemedicine consultations (TMC) of a rheumatological profile, their effectiveness and the main problems that arise during the implementation of this technique.Patients and methods. From June 2020 to December 2021, 102 rheumatological TMCs were performed at the «New Hospital» Medical Association in Yekaterinburg. Patients aged 18–82 years applied for TMC after a face-to-face examination and for the purpose of «pre-consultation». TMC included the following steps: familiarizing the doctor with previous medical reports and the results of examinations; video conference; preparation of final medical report. The Aibolit service and the «Medkarta» platform were used. After TMC, a survey of doctors and patients was conducted to identify the positive and negative aspects of this technique.Results and discussion. Most of the patients who applied for TMC suffered from diseases that required regular monitoring of disease activity (rheumatoid arthritis, psoriatic arthritis, systemic connective tissue diseases), as well as fibromyalgia. Leading reasons for seeking medical advice: exacerbation of the disease or new symptoms onset, the need for laboratory and instrumental monitoring and correction of therapy. The vast majority of patients (90.2%) received answers to all questions and 9.8% – to most of the questions. Doctors had technical problems in 34 (33.3%) cases, including 11 (10.8%) cases when they had to switch to another method of communication.Conclusion. TMK is a promising technique that can be useful and convenient for patients both now, during the COVID-19 pandemic, and in the future. Its main unresolved problems are the recognition of parity between TMK and face-to-face consultations and the improvement of technical conditions.